Ownership and M&A Performance in a Transitional Economy: The Case of the Chinese Real Estate Industry. (5th October 2015) - Yang, Hongyan; Ru, Jing; Ren, Ting
ABSTRACT: In a transitional economy such as China's, when resources are unevenly distributed across different sectors, the disadvantaged sector may seek a growth path that bypasses resource constraints. We investigated this phenomenon in the context of the Chinese real estate industry. By comparing the post–merger and acquisition (M&A) performance of acquiring firms between state-owned enterprises (SOEs) and privately-owned enterprises (POEs), we attempted to show that POEs are better performers in the market should they be granted equitable resources, and the superior performance is strengthened by market-oriented institutional environment. We used M&A events data of publicly listed real estate firms in China from 2004 to 2012, in conjunction with firm characteristics and province-level market environment data. We found the results to be consistent with our hypotheses. In particular, compared to SOEs, privately-owned acquiring firms tend to have better post-M&A performance when both the regions of the acquirer and the target have high level of marketization. The results suggest that the private sector in China's transitional economy is potentially more efficient than the state-owned sector, as long as the market environment is favorable.